PERLINDUNGAN HUKUM TERHADAP PERUSAHAAN ASURANSI DENGAN PERUSAHAAN REASURANSI YANG DICABUT IZIN USAHANYA - Cahyani, Gisella Tiara; Azzahra, Najwa Maulida; Siswajanthy, Farahdinny; Supriyanto, Daffa Amaanullah; Steybi, Fitria Ade (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2024)
The insurance and reinsurance industry plays a crucial role in managing financial risks in society. However, when a reinsurance company that provides protection to insurance companies loses its business license, it can lead to significant legal complexities. This article discusses two critical aspects related to this issue. First, the impact of the revocation of the business license of a reinsurance company on insurance companies and their obligations to policyholders. This situation creates uncertainty regarding the ability of insurance companies to fulfill policyholder claims. Second, how the legal system can provide protection for all parties involved. This includes the role of regulatory authorities in the insurance industry, insurance contract provisions governing rights and obligations, and compensation mechanisms. Emphasis is also placed on the role of legal experts in assisting insurance companies and policyholders in understanding their rights and navigating any necessary legal processes. Through proper legal understanding and protection, market stability in insurance and policyholder trust can be preserved in this complex situation